Свадьба пела и плясала... - Веселовская Ольга Викторовна (От всей души, 2002)
Экземпляры: аб (20150617) / Инвентарный номер: 048602 / Цена: 20.00 / Сис.шифр: 77.056 / Авт.знак: В 38 / ГРНТИ: 13.21 / ББК: 77.056